Quality of Life Variables Assessment, Before and After Pancreatoduodenectomy (PD): Prospective Study - Arvaniti, Maria; Danias, Nikolaos; Theodosopoulou, Eleni; Smyrniotis, Vassilis; Karaoglou, M; Sarafis, Pavlos (My University, 2015)
The treatment of pancreatic cancer is a complex problem, due to late diagnosis, the need for specialized surgical treatment, the large number of relapses and poor survival.
Keywords: Pancreatitis, Chronic; Pain; Chronic pancreatitis